Sosialisasi Pola Hidup Bersih dan Sehat Sebagai Upaya Pencegahan Diare Pada Masyarakat Desa Ciburuy - Zahra, Nisfa; Putra, Muhammad Taqy Dwi; Syarbanu, Lubnatul; Dewi, Putri Alia; Azhari, Fadhillah; Sari, Dini Permata (Universitas 17 Agustus 1945 Jakarta, 2025)
Diarrhea remains a significant public health problem in Indonesia, particularly in rural areas with limited sanitation and clean water access. This community service activity aims to increase the knowledge and awareness of the Ciburuy Village community regarding diarrhea prevention through the promotion of clean and healthy lifestyles (PHBS). The method used was interactive outreach through lectures and discussions, with evaluations in the form of pre- and post-tests. The results of the activity showed a significant increase in participants' knowledge levels, from 63% before the outreach to 100% after the outreach. 91% of participants expressed a commitment to implementing PHBS, particularly handwashing with soap, using healthy latrines, and treating household drinking water. The community response to the activity was very positive, and Posyandu (Integrated Service Post) cadres and local leaders are ready to continue the outreach in their communities. Thus, the PHBS outreach has proven effective in driving changes in community knowledge and attitudes towards diarrhea prevention, although further activities are needed to ensure the long-term sustainability of healthy behaviors.